ANALISIS UNDANG-UNDANG NO. 14 TAHUN 2005 TENTANG GURU DAN DOSEN (Sebuah Kajian Kritis) - Sholikah Sholikah (Akademika, 2017)
Quality and equitable education for Indonesian children is a major capital to get out of the multidimensional crisis. Our nation today has been bored with the phenomenon of poverty that is mainly due to ignorance. The phenomenon should be taken seriously by the government by making policies aimed at creating a good and equitable quality of education for the community. If we look at the current reality that teachers having not met the national standard qualification are about 65%. There have been many teachers not in accordance with their field of expertise, and the main factor is the distribution of teachers mainly centered in urban areas. This is due to the limited ability of the government in improving the welfare of teachers. The government also seeks to put the teachers' status in their ideal position. Teachers' Profession in Law No. 14 of 2005 on Teacher and Lecturer is a profession that is the same as that of doctors, accountants, and Psychologists. To that end, teachers must have a certificate, so they must participate in any certification tests. The law stipulates that the professions of teacher and lecturer are highly respected and their presence is guaranteed. That means teachers and lecturers have been protected by a single legal umbrella that is not easy to change. It also guarantees the authority, self-development, prosperity, recruitment and transfer of teachers and lecturers.